CSIG-21. DE-ORPHANIZING GPR133 - AN ADHESION GPCR REQUIRED FOR GLIOBLASTOMA PROGRESSION. (11th November 2019) - Frenster, Joshua; Erdjument-Bromage, Hediye; Stephan, Gabriele; Chidambaram, Shravanthi; Alghamdi, Abdulhakeem; Bready, Devin; Straeter, Norbert; Liebscher, Ines; Schoeneberg, Torsten; Neubert, Thomas; Placantonakis, Dimitris
Abstract: We previously found GPR133 (ADGRD1), an orphan adhesion GPCR, is de novo expressed in glioblastoma (GBM) and enriched in patient-derived glioblastoma stem cells (GSCs). Knockdown of GPR133 reduces GBM cell proliferation and tumorsphere formation, and abolishes orthotopic tumor initiation in vivo in mice. Analysis of TCGA data indicates that increased GPR133 transcription inversely correlates with patient survival in GBM. While these findings underscore the importance of GPR133 in GBM and suggest an essential role in tumor growth, its ligand and mechanism of activation remain unknown. Toward identifying GPR133 ligands, we used GPR133's N-terminal ectodomain as bait and performed affinity co-immunoprecipitation (CoIP) followed by mass spectrometry as an unbiased screening approach. We identified 490 extracellular proteins with enriched binding to GPR133 compared to control. Reverse CoIP using the 15 most abundant candidate ligands as bait to purify the receptor confirmed this interaction reproducibly in 4 candidates. Despite this binding, overexpression of these candidate ligands, or addition of purified recombinant protein, is not sufficient to increase receptor signaling as assessed by cAMP levels in HEK293 cells. This suggests that ligand binding to the GPR133 ectodomain may not be sufficient by itself to induce receptor activation. We hypothesize receptor activation requires mechanical forces in addition to ligand binding. Consistent with this hypothesis, the GPR133 binding proteins we have identified may be anchored to the extracellular matrix, mediating such mechanical force. To test whether mechanical shearing of the extracellular domain is sufficient for receptor activation, we used Dynabeads coupled to antibody against GPR133's N-terminal ectodomain, and indeed observed receptor activation leading to elevated cAMP levels. No activation was observed when Dynabeads devoid of antibody were used. This mode of GPR133 activation might indicate a role in sensing mechanical/viscoelastic properties of GBM extracellular matrix, which may be relevant to tumor cell migration and invasion.